(untitled) (The Journal of Theoretical Accounting Research, 2026)
This study looks into investors’ cognitive processing and behavioral appraisal of accounting disclosures by ESG and sustainability accounting, as well as gender differences in these assessments. Our study looks at ESG as non-financial accounting information from a decision usefulness, transparency, and disclosure credibility perspective. We analyses how investors assess the credibility of ESG information reported by companies, apart from the application of accounting judgement in valuing investment alternatives. The study uses data from 450 individual investors in Asia-Pacific. Within the framework of this study, a conceptual framework is tested using covariance based structural equation modelling (SEM). The cognitive factors being the financial literacy, risk perceive and objective ESG knowledge, while the behavioral factors include social norm, ethical judgement, and trustee signaling in ESG disclosures affect the usefulness of ESG accounting information and evaluative decision. The paper specifies attitude towards ESG information and perceived return as mediators. Besides, the researchers apply multi-group SEM to test measurement invariance. They further test accounting judgement differences across gender. The model’s output evidence that it had good psychometric properties (χ2/df= 2.18, CFI= 0.95, RMSEA= 0.05, SRMR= 0.04), have good reliability and valid construct (CR ≥ 0.80, AVE≥ 0.50), and have discriminant validity. The structural outcomes point out that both cognitive evaluations (β = 0.32, p < 0.001) and behavioral evaluations (β = 0.45, p < 0.001) are considered significant building blocks to develop ESG disclosure credibility and decision usefulness. Furthermore, attitude toward ESG information partially mediates the relationship between cognitive evaluations and behavioral evaluations and ESG disclosure credibility and decision usefulness. Perceived return plays the weakest mediation role. The analysis of multiple groups shows that behaviour is. This research contributes to sustainability accounting theory and shows how, by understanding ESG as not only an investment attribute but also as sustainability accounting disclosure, disclosure credibility, cognitive interpretation, and ethical judgement jointly determine the decision usefulness of ESG. Results obtained from this study have major implications for ESG reporting frameworks, standard setters and assurance providers requiring enhanced transparency, standardization and credibility in sustainability reporting for investor-oriented accounting outcomes.